The Comparison of Depression Anxiety and Quality of Life Levels Among Trimesters of Pregnancy - Savaş Karataylı; Kazım Gezginç; Faruk Ilgaz; Rengin Karataylı; Ali Savaş Çilli (Medical Network, 2010)
OBJECTIVE: To compare the levels of depression, anxiety and quality of life among trimesters of pregnancy. STUDY DESIGN: A total number of 200 patients;50 pregnant women from each trimester and 50 control group women who are not pregnant but with similar sociodemographic characteristics were included. To determine the levels depressive and anxiety symptoms and quality of life were performed the Beck Depression Inventory (BDI) the Beck Anxiety Inventory (BAI) and the World Health Organization Quality of Life Assessment Brief (WHOQOL-BREF), respectively. RESULTS: While BDE and BAE points in pregnant were indifferent between trimesters; these points were found significantly higher compared with control group. There were significant differences for WHOQOL-BREF and the lowest quality of life was present at 3rd trimester. CONCLUSION: The levels of anxiety and depression were high, and quality of life was low in all trimesters, especially at 3rd trimester. Especially at advanced stages of pregnancy; the health care givers should evaluate pregnant women for depression and anxiety.